The apple does not fall far: stable predictive relationships between parents’ ratings of their own and their children’s self-regulatory abilities - Johanna Kneidinger; José C. García Alanis; Ricarda Steinmayr; Silvia Schneider; Hanna Christiansen (Child and Adolescent Psychiatry and Mental Health)
Abstract Having control over your own behavior and impulses is a critical skill that influences children’s academic, social, and emotional development. This study investigates the stability and predictive relationships between parents’ ratings of their own and their children’s executive function and delay aversion. Using data from approximately 1700 families collected during the COVID-19 pandemic, we employed hierarchical structural equation models and cross-lagged panel models to analyze the temporal stability and directional influences of executive function and delay aversion assessments. Our analysis revealed a substantial latent correlation (r = 0.48, p < 0.001) between parents’ and children’s executive function problems, indicating a shared variance of approximately 23%. Significant cross-lagged effects were found, with parental executive functions at T1 predicting child executive functions at T2 (β = 0.16, p = 0.005). For delay aversion, we found a latent correlation of r = 0.53 (p < 0.001) and significant within-timepoint and temporal stability, but no cross-lagged effects. These findings suggest that higher levels of executive function problems reported by parents at T1 correspond to an increased perception of similar problems in their children at T2. This highlights the importance of parental self-perception in assessing children’s abilities. Our results highlight the importance of incorporating family dynamics into interventions targeting executive function difficulties and delay aversion in children, and understanding this interplay enables the development of more effective, individualized approaches to support positive developmental outcomes.